A brief measure of perceived courtesy and affiliate stigma on COVID-19: A study with a sample from China. (October 2021) - Li, Tingting; Bu, He; Duan, Wenjie
Abstract: The present study aimed to assist public health efforts by developing and conducting psychometric testing of a brief measure of COVID-19-related stigma among people who were potentially but not necessarily infected. All the items were generated and selected based on extensive literature review, participant interviews, and expert evaluations. The psychometric properties were evaluated through performing confirmatory factor analysis tests, exploration structure equation modeling, measurement invariance, internal consistency coefficient, composite reliability, and criterion-related validity, using a sample of 2812 adults (600 male, 2212 female; mean age = 37.23, SD = 6.17) from Hubei Province, China. A clear two-factor structure of the COVID-19-related stigma among people who were potentially but not necessarily infected (i.e., perceived courtesy and affiliate stigma) was identified through the literature review and interviews. Results suggest that the two-factor model of COVID-19-related stigma (5 items for each factor) model fit the data, and the psychometric properties were acceptable. Measurement invariance across gender was supported. A two-factor 10-item scale was finally obtained. Highlights: COVID-19-related stigma can be induced by geographic linkages. COVID-19-related stigma may concern perceived courtesy and/or affiliate stigma. We developed a 10-item, 2-factor COVID-19-related stigma scale. The COVID-19-related stigma scale showed satisfactory psychometric properties. We recommend using the brief COVID-19-related stigma scale in future research.